Reasons and consequences of foreign farmland acquisitions in Latvia : a case study of Aluksne municipality - Apine, Elina (SLU/Dept. of Urban and Rural Development, 2016)
This thesis describes farmland acquisitions by foreign investors in Latvia and explores the historical land reforms and regulations of the land market. Furthermore, the study explores what has caused Latvian farmland to become an attractive investment target for foreign companies, and how these investments affect the countryside and the Latvian farmers. In order to comprehend the economic, social and cultural impacts on the farmers, I have attempted to describe their lifeworlds, by the use of narrative analysis. There is a particular focus on how local farmers experience foreign investments and bureaucratic interventions. The study was conducted in the Alūksne municipality, close to the Russian and Estonian border. The thesis shows how Latvian farmland became an investment target through a land privatisation process, based on a neoliberal market oriented discourse, in the 1990’s. Furthermore, this process increasingly commoditised land and transformed its social and cultural meaning. The investors seldom use farmland for agricultural production, but rather regard it as a source for long-term profit; leasing out the land to local farmers. This has a negative impact on the local economy and creates few employment opportunities. Besides the economic changes local farmers are subjected to constant bureaucratic interventions and policy changes; thus experiencing a high degree of colonisation of their lifeworlds.